MONOLOGUE AND DIALOGUE IN ANTI-CLERICAL CRITICISM AND IN RELIGIOUS PRACTICE - E. O. Gavrilov (Вестник Кемеровского государственного университета, 2013)
The problems of monologue and dialogue as communicative scenarios of religious activity implementation in the modern secular society are investigated in the paper. Dialogue and monologue prospects in religious associations' relations with one another and with the society are analyzed.